Pick Your Portion Sizes - Jennifer Hillan; Claudia Peñuela (EDIS)
Is it tricky to visualize the recommended amounts of foods from the five MyPyramid food groups or determine how much food from each food group you should eat? Since there is not always time or resources for using measuring cups or food scales to help you accurately measure your food, this revised one-page handout helps you picture these amounts, using common household objects for comparison. Written by Jennifer Hillan and Claudia Peñuela, and published by the UF Department of Family Youth and Community Sciences, February 2011.